Effect of raloxifene on lipid profile in postmenopausal women - Bhat, Mufeed Ahmad; Younis, Zohra; Mantoo, Azmat Jahan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Menopause, a natural event in a woman’s life is characterized by loss of reproductive function and decline in estrogen levels. Menopause is not just the cessation of menstruation; it is an outward manifestation of ovarian failure due to depletion of ovarian follicles that leads to decreased estrogen levels which in turn leads to the morbidity associated with the menopause. Objectives were to evaluate serum lipid profile (baseline) of post-menopausal women with menopausal symptoms, to assess the effect of raloxifene on serum lipid levels. Methods: Effects of raloxifene on serum lipid profile were studied in 75 healthy postmenopausal women in a prospective randomized observational study. Serum lipid levels at baseline, 3rd month and 6th month were analyzed using independent samples’ t test. The 95% confidence intervals for the difference in means were reported. Results: At 3 months and 6 months, there was a change of 3.6% and 5.4% respectively, from baseline values in total cholesterol levels, there was change of 3.5% and 5.8% in triglyceride levels from baseline values. There was an increase of 1.4% and 3.5 % from baseline high-density lipoprotein (HDL) levels. There was a decrease of 4.9% and 9.2% from baseline low-density lipoprotein (LDL) levels; 2.6% and 4.4% from baseline VLDL. Conclusions: Our study could lead to good practice of raloxifene in postmenopausal women and help to use Raloxifene with safety and may prevent risks of cardiovascular disease as well as the risk of death from other disease in menopausal women.